Variation in microcytin concentrations in water environment of the Hoan Kiem lake - Thuy, Duong Thi; Cuong, Ho Tu; Kim, Dang Dinh; Quynh, Le Thi Phuong (Academia Journal of Biology, 2012)
The bloom forming cyanobacterium Microcystis aeruginosa is known to produce cyclic heptatoxins (microcystins, MC) which can be toxic to human and animal health. In this paper, we present the results of the determination of microcystin concentrations in the water environment of the Hoan Kiem lake that is the famous location in the center of Hanoi city. The High Performance Liquid Chromatography (HPLC) was used to determine the MC concentrations in water and water bloom samples of the Hoan Kiem lake. The phytoplankton community in the lake composed, mostly of genus Microcystis forming dense mats on the water surface. Two toxin types were extracted and preliminarily identiﬁed as microcystins-LR and RR. The HPLC analytical results showed that the total microcystin content varied between 2.08 and 46.00 µg MC/L. The microcystin contents were higher in dry season (from December/2008 to March/2009) than in rainy season. The occurrence of the toxic cyanobacteria that produce hepatotoxic microcystins as well as microcystin concentrations in the Hoan Kiem lake provide an important information to public health officials. These findings show that it is necessary to monitor the occurrence of toxic cyanobacteria and their toxins in surface water in Vietnam.